2014
DOI: 10.1371/journal.pone.0103286
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction Is Associated with a Tissue-Dependent Reduction of Oxidative Stress in Eusocial Female Damaraland Mole-Rats (Fukomys damarensis)

Abstract: Oxidative stress has been implicated as both a physiological cost of reproduction and a driving force on an animal's lifespan. Since increased reproductive effort is generally linked with a reduction in survival, it has been proposed that oxidative stress may influence this relationship. Support for this hypothesis is inconsistent, but this may, in part, be due to the type of tissues that have been analyzed. In Damaraland mole-rats the sole reproducing female in the colony is also the longest lived. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 81 publications
3
44
0
Order By: Relevance
“…For example, most studies in the meta‐analyses that reported malondialdehyde as a marker of oxidative damage used a spectrophotometric assay that has been criticised for lack of specificity (reviewed by Monaghan et al, ; Selman et al, ), while a few recent studies have used a more precise HPLC method (e.g. Cram et al, ; Schmidt et al, ). Across all tissues and all markers, effect sizes were fairly consistent ( I 2 = 28%) for the relationship between reproductive effort and oxidative damage, while having a high level of heterogeneity ( I 2 = 81%) for the association between reproductive state and oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, most studies in the meta‐analyses that reported malondialdehyde as a marker of oxidative damage used a spectrophotometric assay that has been criticised for lack of specificity (reviewed by Monaghan et al, ; Selman et al, ), while a few recent studies have used a more precise HPLC method (e.g. Cram et al, ; Schmidt et al, ). Across all tissues and all markers, effect sizes were fairly consistent ( I 2 = 28%) for the relationship between reproductive effort and oxidative damage, while having a high level of heterogeneity ( I 2 = 81%) for the association between reproductive state and oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…In wild-derived house mice, the damage to proteins in heart and skeletal muscles did not differ between nonreproducing females and those feeding enlarged or reduced litters, whereas in the liver, the damage either did not differ between these groups or was even decreased in the group with enlarged litters (Aloise Garratt et al, 2013). The results of the few studies on wild-derived small rodents showed that the damage to liver and other organs was unaffected or diminished by rearing nonmanipulated litters (Garratt et al, 2011;Ołdakowski et al, 2012;Schmidt et al, 2014). Interestingly, however, increased damage to proteins was found in the blood serum of reproducing females, even though the same studies showed no increased damage in the organs (Yang et al, 2013;Plumel et al, 2014;Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…; Schmidt et al. ). The biological relevance of this diversity in response is unclear and has often been explained by individual, species, tissue or assay differences, and the difference between studies in the laboratory and field (see Themes 2 and 3 below).…”
Section: Introductionmentioning
confidence: 97%
“…Much of this research has focussed on mammals, mostly rodents, and almost exclusively on females. While some mammalian studies have supported the idea that investment in offspring production (during pregnancy and lactation) causes oxidative damage (Sainz et al 2000;Bergeron et al 2011;Stier et al 2012;Fletcher et al 2013), others have found no effect or that oxidative damage is actually reduced in lactating compared to nonreproducing females (Garratt et al 2011(Garratt et al , 2013Oldakowski et al 2012;Schmidt et al 2014). The biological relevance of this diversity in response is unclear and has often been explained by individual, species, tissue or assay differences, and the difference between studies in the laboratory and field (see Themes 2 and 3 below).…”
Section: Introductionmentioning
confidence: 99%